2018
DOI: 10.3390/en11071704
|View full text |Cite
|
Sign up to set email alerts
|

A Relational Analysis Model of the Causal Factors Influencing CO2 in Thailand’s Industrial Sector under a Sustainability Policy Adapting the VARIMAX-ECM Model

Abstract: Sustainable development is part and parcel of development policy for Thailand, in order to promote growth along with economic growth, social advancement, and environmental security. Thailand has, therefore, established a national target to reduce CO 2 emissions below 20.8%, or not exceeding 115 Mt CO 2 Equivalent (Eq.) by 2029 within industries so as to achieve the country's sustainable development target. Hence, it is necessary to have a certain measure to promote effective policies; in this case, a forecast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
(36 reference statements)
1
7
0
1
Order By: Relevance
“…As for its validity, the model was assessed by white noise testing and goodness of fit. The testing results confirm that the model falls within the accepted standards, availing itself to be the most appropriate model for the study (Sutthichaimethee and Kubaha, 2018a;Sutthichaimethee and Ariyasajjakorn, 2018). The research flow is explained below and is shown in Figure 1.…”
Section: Literature Reviewsupporting
confidence: 59%
“…As for its validity, the model was assessed by white noise testing and goodness of fit. The testing results confirm that the model falls within the accepted standards, availing itself to be the most appropriate model for the study (Sutthichaimethee and Kubaha, 2018a;Sutthichaimethee and Ariyasajjakorn, 2018). The research flow is explained below and is shown in Figure 1.…”
Section: Literature Reviewsupporting
confidence: 59%
“…Thus, although research on economic development and natural capital utilization has become important and widespread, present studies emphasize the conflicting relationship between the natural ecosystem and economic development but neglect their interactive relationship. This omission could then be impacting the expected effects of related public policies (Sutthichaimethee & Kubaha, ). Our research objective looks to answer the following questions: If natural capital utilization and economic development are integrated in the relevant models, will the economic conclusions be different?…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this, the authors conducted other studies to support the forecasting models with different indicators. Those studies are titled "The efficiency of long-term forecasting model on final energy consumption in Thailand's petroleum industries sector: enriching the LT-ARIMAXS Model under a sustainability policy" [91] and "A relational analysis model of the causal factors influencing CO 2 in Thailand's industrial sector under a sustainability policy adapting the VARIMAX-ECM Model" [92]. The mentioned studies used a stationary process, while adapting the concept of a co-integration and error correction mechanism in order to analyze Energies 2019, 12, 3092 8 of 21 the real impact of the indicators on the dependent variable.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It can be observed that the number of parameters in the VAR(1) model is less than the SEM-VARIMAX(1) model's. Even though all the parameters can be estimated in the VAR(1) model, we still cannot use the relationship between the parameters of both models to find the parameter estimator in the SEM-VARIMAX(1) model [91,92].…”
mentioning
confidence: 99%